PHYTOCHEMICAL SCREENING AND FREE RADICAL–SCAVENGING ACTIVITY OF ORTHOSIPHON STAMINEUS (CAT WHISKERS) LEAVES - Sari, Indah Puspita (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2023)
Orthosiphon stamineus, commonly known as